The battle of the socials: Which socially symbolic factors best predict intent to travel?. (October 2018) - Moran, Casey; Boley, B. Bynum; Woosnam, Kyle M.; Jordan, Evan J.; Kline, Carol; Knollenberg, Whitney
Abstract: Tourists are flooded with travel options making competition fierce within their consideration sets. While most research emphasizes the functional attributes of destinations, as narcissism becomes more normalized, it is of increasing interest to examine the influence socially symbolic factors have on tourist decision making. Therefore, this study sought to examine the efficacy of four different socially symbolic predictors of travel—social norms, social self-concept (actual and ideal), and social return—for predicting a person's likelihood to travel to Cuba across three time horizons (1 year, 5 years, and 10 years). Results from a panel of 785 U.S. travelers found social norms to be the best predictor of travel across all three time horizons with social return also being significant across all time horizons. Implications to destination marketing are discussed such as some socially symbolic variables being easier to operationalize in marketing campaigns compared to others (e.g. social return vs. social norms). Highlights: Socially symbolic factors compared to see which one best predicts intent to travel. Socially symbolic factors explain over 50% of variance in intent to travel. Socially symbolic factors less influential over longer time horizons. Social norms is the best symbolic predictor yet may be hard to market toward. Marketing toward social return and self-concept suggested to trigger travel.